2006
DOI: 10.1128/jcm.44.2.324-326.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Micafungin against 315 Invasive Clinical Isolates of Fluconazole-Resistant Candida spp

Abstract: Micafungin is a new echinocandin exhibiting broad-spectrum activity against Candida spp. The activity of the echinocandins against Candida species known to express intrinsic or acquired resistance to fluconazole is of interest. We determined the MICs of micafungin and caspofungin against 315 invasive clinical (bloodstream and other sterile-site) isolates of fluconazole-resistant Candida species obtained from geographically diverse medical centers between 2001 and 2004. MICs were determined using broth microdil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 18 publications
(20 reference statements)
1
63
0
2
Order By: Relevance
“…However, the MICs were read after 48 h of incubation rather than 24 h. Recently, we have tested a smaller collection of 315 fluconazole-resistant isolates of Candida spp. using the CLSI consensus conditions and found excellent activity for both micafungin and caspofungin (6). Although the echinocandins appear to have excellent activity against Candida spp., recent reports describing the development of resistance to caspofungin and micafungin during treatment of endocarditis (7) and to caspofungin during treatment of esophagitis (4) raise the specter of the emergence of echinocandin-resistant Candida species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the MICs were read after 48 h of incubation rather than 24 h. Recently, we have tested a smaller collection of 315 fluconazole-resistant isolates of Candida spp. using the CLSI consensus conditions and found excellent activity for both micafungin and caspofungin (6). Although the echinocandins appear to have excellent activity against Candida spp., recent reports describing the development of resistance to caspofungin and micafungin during treatment of endocarditis (7) and to caspofungin during treatment of esophagitis (4) raise the specter of the emergence of echinocandin-resistant Candida species.…”
mentioning
confidence: 99%
“…In the present study we have employed the optimal testing conditions described previously (6,9,14), to examine geographic trends in the activity of micafungin against an interna- 3 of Candida pelliculosa, and 1 each of Candida rugosa and Candida zeylanoides. All isolates were obtained from blood or other normally sterile sites and represented individual infectious episodes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one study of 315 fluconazoleresistant isolates, the overall MIC90 was 0.06 mcg/mL; C. glabrata isolates were the most sensitive to micafungin, with an overall MIC90 of 0.015 mcg/mL for 110 isolates (22). A second study also found excellent activity against all species of Candida, although MICs for C. parapsilosis were among the highest, ranging from 0.5 to 2 mcg/mL (23).The third study found micafun- Table 1.…”
Section: Micafungin Vs Candidamentioning
confidence: 99%
“…Three studies evaluated the in vitro activity of micafungin against 551 clinical Candida isolates (22,23,35). In one study of 315 fluconazoleresistant isolates, the overall MIC90 was 0.06 mcg/mL; C. glabrata isolates were the most sensitive to micafungin, with an overall MIC90 of 0.015 mcg/mL for 110 isolates (22).…”
Section: Micafungin Vs Candidamentioning
confidence: 99%